Diabetic retinopathy diagnostic with ophthalmoscope by trained doctor - Hartono, Imam Masduki Angela Nurini Agni (Universitas Gadjah Mada, 2008)
Introduction. Diabetes mellitus patient is in high risk to be complicated by retinopathy. Visual loss and decrease of visual acuity become a significant social burden. Early detection is essensial for treatment. Ophthalmoscopy was highly effective for screening, easily used and accessed by ophthalmologist and other physician and has been applied in many developed countriesPurpose : This study was aimed to know the validity of ophthalmoscopic test done by a trained doctor in diagnosing diabetic retinopathy..Materials and methods : The subjects were diabetic patients without cataracts. The examiner was a resident of Internal Medicine Department who had been trained in ophthalmoscopy. After the training, the resident was assessed and the result was compared with the trainer and showed agreement with kappa 1.00.Results: The study was done from February to May 2007. Total subjects were 98 patients (196 eyes I consisted of 50 females (51%1 and 48 males (49%1 with mean age of 61 :t7.92 years old. Mean diabetes duration was 6.6:t 5.94 years and all of them were diabetes type 2. Some patients had hypertension (44.9%1, dyslipidemia (17.7%1, heart disease (6.1%), and kidney disease (5.1%1. From 196 eyes, 6 (6.1 %1 eyes had cataract and were excluded. Mean visual acuity was 0.7726 :to.31 08. Diabetic retinopathy was found in 41 eyes among 190 eyes (21.57%1, consisted of 22 eyes with mild NPDR (53.65%1, 7 eyes with moderate NPDR (17.07%), 7 eyes with severe NPDR (17.07%1, 5 eyes with advance PDR (12.19%1. Sensitivity, specificity, PPV, NPV and accuracy resulted by 5 hour trained doctor examinations were 63.41%, 67.78%, 36.62%, 67.78%, and 66.78% respectively R (+1 and LR (-I were 1.968 and 0.5397, respectively.Conclusion: Direct ophthalmoscopic examination by a trained doctor to detect retinopathy is promisalble in Indonesia.Keywords : diabetic retinopathy, direct ophthalmoscopy, diagnostic value, traineddoctor